Fabrication Strategies for Bioceramic Scaffolds in Bone Tissue Engineering with Generative Design Applications - KURT, MUSTAFA; GÜNDÜZ, OĞUZHAN (My University, 2024)
The aim of this study is to provide an overview of the current state-of-the-art in the fabrication of bioceramic scaffolds for bone tissue engineering, with an emphasis on the use of three-dimensional (3D) technologies coupled with generative design principles. The field of modern medicine has witnessed remarkable advancements and continuous innovation in recent decades, driven by a relentless desire to improve patient outcomes and quality of life. Central to this progress is the field of tissue engineering, which holds immense promise for regenerative medicine applications. Scaffolds are integral to tissue engineering and serve as 3D frameworks that support cell attachment, proliferation, and differentiation. A wide array of materials has been explored for the fabrication of scaffolds, including bioceramics (i.e., hydroxyapatite, beta-tricalcium phosphate, bioglasses) and bioceramic–polymer composites, each offering unique properties and functionalities tailored to specific applications. Several fabrication methods, such as thermal-induced phase separation, electrospinning, freeze-drying, gas foaming, particle leaching/solvent casting, fused deposition modeling, 3D printing, stereolithography and selective laser sintering, will be introduced and thoroughly analyzed and discussed from the point of view of their unique characteristics, which have proven invaluable for obtaining bioceramic scaffolds. Moreover, by highlighting the important role of generative design in scaffold optimization, this review seeks to pave the way for the development of innovative strategies and personalized solutions to address significant gaps in the current literature, mainly related to complex bone defects in bone tissue engineering.
Keywords: Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Mühendislik; Malzeme Bilimi; Mikrobiyoloji; MALZEME BİLİMİ, BİYOMATERYAL; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); ENGINEERING; MATERIALS SCIENCE; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; MATERIALS SCIENCE, BIOMATERIALS; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Biyomalzemeler; Biyokimya; Biyomedikal mühendisliği; Moleküler Tıp; Bioengineering; Physical Sciences; Biomaterials; Biochemistry; Molecular Medicine; 3D scaffold; bioceramics; bone tissue engineering; composites; generative design